2017
DOI: 10.1175/jhm-d-17-0062.1
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Heat Fluxes during an Extreme Lake-Effect Snow Event

Abstract: Proper modeling of the turbulent heat fluxes over lakes is critical for accurate predictions of lake-effect snowfall (LES). However, model evaluation of such a process has not been possible because of the lack of direct flux measurements over lakes. The authors conducted the first-ever comparison of the turbulent latent and sensible heat fluxes between state-of-the-art numerical models and direct flux measurements over Lake Erie, focusing on a record LES event in southwest New York in November 2014. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 54 publications
(66 reference statements)
0
31
0
Order By: Relevance
“…Finite Volume Community Ocean Model (FVCOM) (Chen et al ) is used in this study, which is an unstructured‐grid, finite‐volume, three‐dimensional (3D), primitive equation ocean model. FVCOM's unstructured‐grid feature allows for flexible geometrical fitting and local topography refinement, which has proven successful for research and applications to estuaries, coastal oceans, and Lakes (Xue et al , , ; Anderson and Schwab ; Beardsley et al ; Fujisaki‐Manome et al ; Safaie et al ). The horizontal resolution of the model grids varies from ∼ 1 km near the coast to 5 km in the offshore regions of the lake (Fig.…”
Section: Model Description and Design Of The Experimentsmentioning
confidence: 99%
“…Finite Volume Community Ocean Model (FVCOM) (Chen et al ) is used in this study, which is an unstructured‐grid, finite‐volume, three‐dimensional (3D), primitive equation ocean model. FVCOM's unstructured‐grid feature allows for flexible geometrical fitting and local topography refinement, which has proven successful for research and applications to estuaries, coastal oceans, and Lakes (Xue et al , , ; Anderson and Schwab ; Beardsley et al ; Fujisaki‐Manome et al ; Safaie et al ). The horizontal resolution of the model grids varies from ∼ 1 km near the coast to 5 km in the offshore regions of the lake (Fig.…”
Section: Model Description and Design Of The Experimentsmentioning
confidence: 99%
“…To date, this step has been achieved; a small network of in situ eddy-covariance stations was deployed across the Great Lakes through an initiative launched by the International Joint Commission Spence et al, 2011) in the mid-to late-2000s, and the measurements have been used to validate the algorithms encoded in the operational models (Charusombat et al, 2018;Deacu et al, 2012;Fujisaki-Manome et al, 2017). First, in situ eddy-covariance stations needed to be deployed across the Great Lakes to (among other objectives) assess and refine the intrinsic flux algorithms in the models.…”
Section: 1029/2019gl082289mentioning
confidence: 99%
“…First, in situ eddy-covariance stations needed to be deployed across the Great Lakes to (among other objectives) assess and refine the intrinsic flux algorithms in the models. To date, this step has been achieved; a small network of in situ eddy-covariance stations was deployed across the Great Lakes through an initiative launched by the International Joint Commission Spence et al, 2011) in the mid-to late-2000s, and the measurements have been used to validate the algorithms encoded in the operational models (Charusombat et al, 2018;Deacu et al, 2012;Fujisaki-Manome et al, 2017).…”
Section: 1029/2019gl082289mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent lake studies have found that declining duration of ice cover over the lakes and increasing lake surface water temperatures (Mason et al, ) have caused major summer convective storm water impacts in Midwestern cities (Kessler, ). Other meteorological impacts include wintertime lake‐effect snow in coastal communities, induced by rapid heat and moisture exchange over the Great Lakes (Fujisaki‐Manome et al, ). For example, in November 2014, an extreme lake‐effect storm in Buffalo, New York, delivered more than seven feet of snow due to sustained lake‐effect conditions.…”
Section: Potential Benefitsmentioning
confidence: 99%